Massive spatial qubits: Testing macroscopic nonclassicality and Casimir entanglement - Bin Yi; Urbasi Sinha; Dipankar Home; Anupam Mazumdar; Sougato Bose (Physical Review Research, 2023)
An open challenge in physics is to expand the frontiers of the validity of quantum mechanics by evidencing nonclassicality of the center of mass state of a macroscopic object. Yet another equally important task is to evidence the essential nonclassicality of the interactions which act between macroscopic objects. Here we introduce a new tool to meet these challenges: massive spatial qubits. In particular, we show that if two distinct localized states of a mass are used as the |0〉 and |1〉 states of a qubit, then we can measure this encoded spatial qubit with a high fidelity in the σ_{x},σ_{y}, and σ_{z} bases simply by measuring its position after different duration of free evolution. This technique can be used reveal the irreducible nonclassicality of the spin and center of mass entangled state of a nanocrystal implying macrocontextuality. Further, in the context of Casimir interaction, this offers a powerful method to create and certify non-Gaussian entanglement between two neutral nano-objects. The entanglement such produced provides an empirical demonstration of the Casimir interaction being inherently quantum.